ENHANCING CYBERSECURITY WITH ARTIFICIAL INTELLIGENCE: TRENDS AND CHALLENGES - Rajshree (ShodhKosh: Journal of Visual and Performing Arts, 2023)
As technology advances rapidly, cybersecurity has become an essential component of the modern digital world. This paper examines the role of Artificial Intelligence (AI) in strengthening cybersecurity, focusing on its ability to predict, prevent, and respond to cyber threats. We highlight the latest trends, including AI-driven threat detection, anomaly detection, and automated incident management. At the same time, we delve into the challenges that AI faces, such as ethical issues, adversarial attacks, and data privacy concerns. Through case studies and experimental findings, we demonstrate the effectiveness of AI in addressing evolving cyber threats. The paper aims to guide the integration of AI into cybersecurity frameworks, ensuring a secure digital environment.